Legality of Indonesian Cryptocurrency Trading in the Era of Globalization - Firmansyah; Muryanto, Yudho Taruno (International Journal of Sustainability in Research, 2024)
The rapid development of cryptocurrencies does not rule out the possibility of criminal activity. Crypto currency developers seize investors' assets, causing investors to lose their assets, which is commonly known as "rug pull". Therefore, this research aims to analyze the legality of cryptocurrencies based on the regulations in force in Indonesia and the legality of cryptocurrency exchanges in Indonesia. The type of research method used in this research is normative legal research, by studying the laws and regulations in force in Indonesia, the opinions of ulama, and legal theories, using conceptual methods and approaches through statutory regulations, and using legal materials. collected through literature research, and by improving the law Clarifying the requirements for cryptocurrency as an investment vehicle in Indonesia, using legal material processing techniques.